Unlocking Business Competitiveness: The Role of Entrepreneurial Skills, CRM, and Product Diversification in Coastal Areas - Abdullah, Muhamad Al Faruq; Doktoralina, Caturida Meiwanto; Febrian, Wenny Desty; Maulana, Diky; Prayogo, Dhani Adi (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This study explores the determinants of Business Competitiveness (BC) among female entrepreneurs in coastal areas by examining the influence of Entrepreneurial Skills (ES), Customer Relationship Management (CRM), and Product Diversification (PD). The research also identifies structural challenges including limited market access, technological constraints, and reliance on seasonal or resource-dependent industries.Methodology: The study adopts a quantitative approach using Structural Equation Modelling–Partial Least Squares (SEM-PLS) to analyse the relationships between ES, CRM, PD, and BC. The analysis includes coefficients and p-values to validate the significance of each relationship. Data were gathered from 120 female entrepreneurs in coastal regions using structured questionnaires that captured responses related to each construct. The model also includes an assessment of the mediating effect of PD on the relationship between ES, CRM, and BC.Finding: The findings indicate that both ES and CRM positively and significantly affect BC, both directly and through the mediating influence of PD. ES enhances adaptive decision-making and market-oriented innovation, while CRM strengthens customer relationships and retention. PD enables firms to broaden offerings, thereby improving responsiveness to consumer demands and mitigating market uncertainty. These results align with Doktoralina et al., who emphasised the role of digital transformation and innovation in increasing coastal SME resilience.Conclusion: ES and CRM contribute substantially to business competitiveness, with PD serving as a mediating mechanism that enhances their effects. Strengthening entrepreneurial capacity, fostering customer-focused strategies, and applying product diversification practices are necessary steps for improving the competitiveness of women-led businesses in coastal areas.